The Influence of Frames of Reference in Understanding Covid-19 in Zimbabwe - Ashton Mudzingiri; Hugh Mangeya (UNISA Press, 2022)
The study unpacks some of the frames of reference that people use to explain and understand Covid-19 in Zimbabwe. The study used a qualitative research approach to explore participants’ frames of reference. A phenomenological research design was adopted. Purposive sampling was used to select research participants, whilst two online focus group discussions were held. Data were collected through the use of semi-structured interview questions, which were administered online. The study revealed five salient themes as frames of reference, each with its own sub-themes. These are religion, politics, race, the rural–urban dichotomy, and age. The study concluded that people use their frames of reference to understand pandemics. Certain myths about Covid-19 emanate from people's frames of reference, without any scientific basis. It was also noted that frames of reference give rise to the construction and perpetuation of misinformation, disinformation, and conspiracy theories. It is recommended that stakeholders take a systematic and integrated approach which appeals to all people's frames of reference when disseminating information.